Analysis of the Implementation of Remedial Biology Learning in the Kurikulum Merdeka - Safitri, Ella; Narsan, Vifty Octanarlia (Biotik, 2025)
This research was conducted to see the implementation of remedial learning in the independent curriculum at 12 high schools in Central Lampung District. The method used is descriptive qualitative with purposive sampling technique. The results of the research analysis of the feasibility of remedial biology learning in the Independent Curriculum in State High Schools in 12 sub-districts of Central Lampung Regency have carried out and implemented remedial learning in the good category. Analysis of the data obtained in the discussion section can be concluded that from the 4 indicators of teachers at the remedial learning stage, namely identifying remedial learning problems, creating remedial learning plans, implementing remedial learning, and evaluating the process and results of remedial learning, it shows good criteria. Meanwhile, 15 student statements regarding the implementation of Biology remedial learning showed an average score in the good category.Keywords: Biology; Independent Curriculum; Remedial Learning